Biosorption of Au(III) and Cu(II) from aqueous solution by a non-living Usnea longissima biomass - Turhan, K; Ekinci-Dogan, C; Akcin, G; Aslan, A (Parlar Research & Technology UG, 2005)
The preconcentration of trace copper and gold from aqueous solutions by Flame Atomic Absorption Spectrometry (FAAS) determination was studied by using lichen (Usnea longissinia), as a biosorbent. Biosorption of Au (III) and Cu (II) from dilute aqueous solutions by biomass of the lichen Usnea longissima was investigated. The removal and recovery of gold and copper were studied by applying batch technique. The experimental parameters which are the pH of the solution, stirring time, the amount of lichen, the concentration of metals on retention and elution have been investigated. Gold and copper were adsorbed on lichen at pH 2 and pH 8, respectively. Quantitative retention (between 94% and 99%) was obtained within 75 minutes for both metals. Maximum capacity of 1.0 g of dried lichen for biosorption of Au(III) and Cu(II) were found as 9.4 mg of Au(III) and 24.0 mg of Cu(II). It was seen that the adsorption equilibrium data conformed well to the Langmuir model and Freundlich equation for Au(III) and Cu(II). The method proposed in this study was applied to spring mineral water analysis and metals adsorbed on the lichens were quantitatively (>= 90%) recovered from mineral water samples by using 0.5 mol.L-1 hydrochloric acid.
Keywords: biosorption; metal removing; Usnea longissima; FAAS; adsorption isotherms; TURKEY; LICHENS; REMOVAL; REGIONS; ARTVIN; COPPER; WATER; Environmental Sciences & Ecology